2022
DOI: 10.3389/fnagi.2022.899678
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a Potential Neuroprotectant: Mechanisms in Subarachnoid Hemorrhage-Induced Early Brain Injury

Abstract: Subarachnoid hemorrhage (SAH) is a common cerebrovascular disease with high mortality and disability rates. Despite progressive advances in drugs and surgical techniques, neurological dysfunction in surviving SAH patients have not improved significantly. Traditionally, vasospasm has been considered the main cause of death and disability following SAH, but anti-vasospasm therapy has not benefited clinical prognosis. Many studies have proposed that early brain injury (EBI) may be the primary factor influencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…It is well known that traumatic or spontaneous deep brain centers hematomas or ischemia can cause extrapyramidal sypmtoms. [1][2][3] It is very interesting that the subthalamic nucleus has not been adequately studied in subarachnoid hemorrhages. Anosmia and ageusia have been recognized as the earliest, most common, and most frequent non-motor symptoms of Parkinson's disease, and all theories are based on this idea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that traumatic or spontaneous deep brain centers hematomas or ischemia can cause extrapyramidal sypmtoms. [1][2][3] It is very interesting that the subthalamic nucleus has not been adequately studied in subarachnoid hemorrhages. Anosmia and ageusia have been recognized as the earliest, most common, and most frequent non-motor symptoms of Parkinson's disease, and all theories are based on this idea.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently become clear that cerebral ischemic insults and subarachnoid hemorrhage should be considered as important etiological factors in the etiology of Alzheimer's and Parkinson's disease. [1] It is well known that traumatic or spontaneous deep brain centers hematomas or ischemia can cause extrapyramidal sypmtoms. [2,3] Parkinson's disease is accompanied by neurodegeneration, neuronal loss, reactive gliosis and synuclein (Lewy bodies) accumulation occurs in the substantia nigra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the regulation of the endocrine system also plays an important role in the treatment of PD, including sex hormones, insulin, and melatonin [69][70][71][72]. According to the docking results, it is speculated that YGJ-BBB may act on ERBB2, ESR1, ESR2, IGF1R, MAP2K1, and MAPK1 targets to intervene endocrine resistance.…”
Section: Discussionmentioning
confidence: 99%